Indonesia: Growth Performance and Policy Challenges - de Mello, Luiz (OECD Economics Department Working Papers, 2008)
Indonesia's growth performance is improving, following a slow recovery from the 1997-98 financial crisis. Investment is picking up, despite considerable business-climate obstacles to entrepreneurship. Unemployment remains high, and labour informality is pervasive. Fiscal policy has been conducted responsibly and in an increasingly decentralised manner. Monetary policy is now carried out within a fully-fledged inflation-targeting framework. This paper argues that the main barriers to raising the economy's growth potential are to be found on the supply side of the economy. Indonesia will need to improve the business environment and to make better use of labour inputs to put the economy on a higher growth trajectory. The country's income gap relative to the OECD is sizeable, and several years of sustained growth will be needed to eliminate it. This Working Paper relates to the 2008 OECD Economic Assessment of Indonesia (www.oecd.org/eco/surveys/indonesia)